Factors influencing specialist outreach and support services to rural populations in the Eden and Central Karoo districts of the Western Cape - Johan Schoevers; Louis Jenkins (AOSIS, 2015)
Background: Access to health care often depends on where one lives. Rural populations have significantly poorer health outcomes than their urban counterparts. Specialist outreach to rural communities is one way of improving access to care. A multifaceted style of outreach improves access and health outcomes, whilst a shifted outpatients style only improves access. In principle, stakeholders agree that specialist outreach and support (O&S) to rural populations is necessary. In practice, however, factors influence whether or not O&S reaches its goals, affecting sustainability. Aim and setting: Our aim was to better understand factors associated with the success or failure of specialist O&S to rural populations in the Eden and Central Karoo districts in the Western Cape. Methods: An anonymous parallel three-stage Delphi process was followed to obtain consensus in a specialist and district hospital panel. Results: Twenty eight specialist and 31 district hospital experts were invited, with response rates of 60.7% - 71.4% and 58.1% - 74.2% respectively across the three rounds. Relationships, communication and planning were found to be factors feeding into a service delivery versus capacity building tension, which affects the efficiency of O&S. The success of the O&S programme is dependent on a site-specific model that is acceptable to both the outreaching specialists and the hosting district hospital. Conclusion: Good communication, constructive feedback and improved planning may improve relationships and efficiency, which might lead to a more sustainable and mutually beneficial O&S system.